The Role of Heme Oxygenase-1 as an Immunomodulator in Kidney Disease - Virginia Athanassiadou; Stella Plavoukou; Eirini Grapsa; Maria G. Detsika (MDPI AG, 2022)
The protein heme oxygenase (HO)-1 has been implicated in the regulations of multiple immunological processes. It is well known that kidney injury is affected by immune mechanisms and that various kidney-disease forms may be a result of autoimmune disease. The current study describes in detail the role of HO-1 in kidney disease and provides the most recent observations of the effect of HO-1 on immune pathways and responses both in animal models of immune-mediated disease forms and in patient studies.